2021
DOI: 10.1021/acs.bioconjchem.0c00673
|View full text |Cite
|
Sign up to set email alerts
|

Dual Site-Specific Chemoenzymatic Antibody Fragment Conjugation Using CRISPR-Based Hybridoma Engineering

Abstract: Functionalized antibodies and antibody fragments have found applications in the fields of biomedical imaging, theranostics, and antibody–drug conjugates (ADC). In addition, therapeutic and theranostic approaches benefit from the possibility to deliver more than one type of cargo to target cells, further challenging stochastic labeling strategies. Thus, bioconjugation methods to reproducibly obtain defined homogeneous conjugates bearing multiple different cargo molecules, without compromising target affinity, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 41 publications
0
19
0
Order By: Relevance
“…Many site-specific antibody drug conjugation technologies have been developed by coupling the cytotoxin to engineered specific amino acids, unnatural amino acids, short peptide tags, and N297 glycans . In this study, we chose the Fab, which has more advantages in permeability and cost control than full-length antibodies, as the ADC carrier. , The site-specifically engineered cysteine and an unnatural amino acid ( p -acetyl-phenylalanine) were designed as conjugation sites on Fab. We innovated a new method for sequentially conjugating two distinct small molecules onto one antibody fragment using oxime ligation and Michael addition in a site-specific manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many site-specific antibody drug conjugation technologies have been developed by coupling the cytotoxin to engineered specific amino acids, unnatural amino acids, short peptide tags, and N297 glycans . In this study, we chose the Fab, which has more advantages in permeability and cost control than full-length antibodies, as the ADC carrier. , The site-specifically engineered cysteine and an unnatural amino acid ( p -acetyl-phenylalanine) were designed as conjugation sites on Fab. We innovated a new method for sequentially conjugating two distinct small molecules onto one antibody fragment using oxime ligation and Michael addition in a site-specific manner.…”
Section: Discussionmentioning
confidence: 99%
“…Kumar et al reported the development of a heterotrifunctional linker to generate a dual-drug ADC with MMAE and pyrrolobenzodiazepine dimer (PBD dimer) . Recently Le Gall et al reported a CRISPR/Cas9-based strategy to rapidly engineer hybridoma cells to secrete Fab bearing two distinct site-specific labeling motifs, which can be separately modified by two different sortases . Xiao et al developed a general method for generating ADCs containing two distinct drugs or a combination of a drug and an imaging agent with the incorporation of two uniquely reactive UAAs (with keto and azido side chains) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[H-GGGCK(FITC)-NH 2 ] and [H-GGGK(N 3 )-NH 2 ] synthesis was described elsewhere 48 . For [GGGK(N 3 )FRSLLMWITQ(Abu)] synthesis, 25 mL polypropylene syringes with a porous disc were used for solid-phase peptide synthesis (SPPS).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, cell-free protein synthesis has emerged as an attractive candidate to produce more homogenous ADCs by introducing payloads at one or more defined sites, thus developing more stable and less toxic ADCs [ 144 ]. A gene engineering technology, the CRISPR/Cas-9 system, offers the opportunity to engineer Fab molecules and allows for dual site-specific conjugation without compromising target affinity [ 145 ]. Harnessing the platform to produce Fab fragments and be equipped with two distinct cytotoxic payloads appears to be a promising option to obtain a better therapeutic outcome while reducing the toxicity of the combination therapy.…”
Section: Future Perspectivesmentioning
confidence: 99%